SiCf / SiC composite material containing high-strength and high-modulus matrix as well as preparation method and application of SiCf / SiC composite material

By introducing SiC whiskers and nano-silica powder-modified polycarbonsilane slurry in SiCf/SiC composite materials by gel injection molding, a continuous rigid carrier skeleton was formed, which solved the problems of loose matrix distribution and defects, significantly improved the Mechanical properties and manufacturing cost efficiency of composite materials.

CN119430970AActive Publication Date: 2025-02-14NORTHWESTERN POLYTECHNICAL UNIV

Patent Information

Application Number
CN202411030692.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-30
Publication Date
2025-02-14
Estimated Expiration
2044-07-30

AI Technical Summary

Technical Problem

The matrix of existing SiCf/SiC composites has problems such as loose distribution, difficulty in continuous loading, as well as high defects, low crystallinity and impure components, which limit the improvement of its strength and modulus.

Method used

The gel injection molding method is used to introduce high volume fraction SiC whiskers, and nano-silica powder-modified polycarbonsilane slurry is introduced through vacuum impregnation and pressure impregnation to form a continuous rigid carrier skeleton to improve the defect content and crystals of the matrix. degree of purity and component.

Benefits of technology

The matrix strength and modulus of SiCf/SiC composite materials are significantly improved, the mechanical properties are improved, the problem of poor loading efficiency of the matrix is ​​solved, and the manufacturing cost is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119430970A_ABST
    Figure CN119430970A_ABST
Patent Text Reader

Abstract

The invention discloses a SiCf / SiC composite material containing a high-strength and high-modulus matrix as well as a preparation method and application of the SiCf / SiC composite material, and relates to the technical field of silicon carbide-based composite materials. The method comprises the following steps: preparing a CVI-BN interface phase in a SiC fiber preform by adopting a chemical vapor infiltration process, and introducing SiC whiskers into the SiC fiber preform by adopting a gel casting process to obtain a porous composite material; the porous composite material is placed in first polycarbosilane slurry for multiple times of dipping and cracking, and a semi-compact SiCf / SiC composite material is obtained; the semi-compact SiCf / SiC composite material is placed in second polycarbosilane slurry for multiple times of dipping and cracking, and a compact SiCf / SiC composite material is obtained; according to the invention, the inert filler SiCw and the active filler silicon powder are combined to jointly modify the PIP-SiC matrix, so that a continuous rigid transfer skeleton is formed in the matrix, the defect content of the matrix is reduced, the crystallization degree is improved, and the components are purified. The mechanical property of the modified composite material is improved by more than 30%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of silicon carbide-based composite materials, and in particular to a SiC composite material containing a high-strength and high-modulus matrix. f / SiC composite material and its preparation method and application. Background Art

[0002] The hot end components of the new generation of aircraft engines serve in harsh environments with higher temperatures, are in direct contact with high-temperature combustion gases, are susceptible to combustion gas corrosion, and are subjected to strong aerodynamic and thermal fatigue loads. f / SiC) has become an important candidate material for the hot end components of the new generation of high-performance aircraft engines due to its excellent properties such as high specific strength and good temperature resistance.

[0003] SiC f The preparation methods of SiC / SiC composite materials mainly include chemical vapor infiltration (CVI), precursor impregnation pyrolysis (PIP), reactive melt infiltration (RMI) and the combination of the above methods. The equipment cost of CVI method is high and the prepared SiC f / SiC composite materials have a large open porosity (10% to 15%) and are prone to failure in high-temperature corrosive environments. f / SiC composite materials usually contain a large amount of residual silicon (>10%). When the temperature exceeds the softening point or melting point of Si, the performance drops sharply, making it difficult to adapt to the high temperature and high stress conditions of aircraft engines. The PIP method has relatively low cost, adjustable preparation temperature, less damage to the fiber, and the prepared SiC f / SiC composite materials have low open porosity (~10%) and can be manufactured into complex-shaped components, making them a low-cost method for preparing high-density SiC f Common methods for preparing SiC composites.

[0004] In SiC f In SiC composite materials, the matrix plays important roles in load transfer, shaping, and protecting SiC fibers. Among them, efficient transfer of load to SiC fibers is the key to achieving SiC f / SiC composite materials are the key to high performance. Efficient loading requires the matrix to have high strength and high modulus characteristics. The PIP method requires multiple rounds of impregnation and cracking to prepare highly dense composite materials, which results in a loose distribution of the PIP-SiC matrix and difficulty in continuous loading. In addition, the PIP-SiC matrix is ​​transformed from the polymer precursor polycarbosilane (PCS), and its structure is usually amorphous. In addition, it inevitably produces a violent shrinkage during the ceramicization process, accompanied by the escape of small molecular gases, resulting in cracks and micropores inside the PIP-SiC matrix. At the same time, a small amount of aromatic hydrocarbons are difficult to escape during the cracking of PCS and remain inside the matrix, resulting in free carbon in the PIP-SiC matrix. The free carbon itself has a low modulus and is prone to cracks. In summary, the PIP-SiC matrix is ​​loosely distributed, difficult to load continuously, and the matrix has problems such as high defects, low crystallinity, and impure components, which seriously limits the improvement of the matrix strength and modulus and affects the loading efficiency of the matrix. Therefore, improving the continuity of the PIP-SiC matrix and improving the defect content, crystallinity and composition of the matrix are the key to achieving SiC f The key to the high performance of SiC composites.

[0005] At present, the methods to improve the properties of PIP-SiC matrix mainly include adding inert fillers or active fillers. Inert fillers mainly include SiC particles (SiC p )、SiC whiskers(SiC w ) and SiC nanowires (SiC nws ), etc. Active fillers mainly include Al, Ti and other powders. Common filler introduction methods are mainly slurry impregnation and CVI technology. Inert fillers: When slurry impregnation technology is used to introduce high volume fraction inert fillers, SiC f A large number of closed pores are formed inside the SiC composite material, and the density decreases; CVI technology is used to grow SiC in situ w or SiC nws , it is difficult to achieve a high volume fraction, and the CVI equipment is expensive and the process cost is high. Both methods have certain limitations in regulating and increasing the introduction content of fillers, and it is difficult to improve the continuity of the matrix. In terms of active fillers: There is a mismatch in thermal expansion coefficients between heterogeneous fillers such as Al and Ti and SiC, which exacerbates the problem of impure components in the PIP-SiC matrix. Residual stress will be generated during the preparation of the matrix, affecting the SiC f In summary, the currently developed modification methods are difficult to simultaneously solve the problems of loose distribution of PIP-SiC matrix, difficulty in continuous loading, high matrix defects, low crystallinity and impure components. Summary of the invention

[0006] In view of the shortcomings of the above-mentioned background technology, the present invention mainly solves the problems that the existing modification methods are difficult to solve at the same time, such as loose distribution of PIP-SiC matrix, difficulty in continuous loading, high matrix defects, low crystallinity and impure components. The present invention provides a SiC matrix with high strength and high modulus. f / SiC composite material and its preparation method and application. The present invention adopts gel injection molding method to form high volume fraction SiC w The nano-silicon powder-modified polycarbosilane slurry is introduced into the SiC preform to promote the formation of a continuous rigid skeleton inside the matrix, and the nano-silicon powder-modified polycarbosilane slurry is introduced into the SiC preform by vacuum impregnation and pressure impregnation. f / SiC composites, the defect content, crystallinity and composition of the PIP-SiC matrix were improved.

[0007] The first object of the present invention is to provide a SiC matrix having high strength and high modulus f A method for preparing a SiC composite material comprises the following steps: The CVI-BN interface phase was prepared in the SiC fiber preform by chemical vapor infiltration process, and SiC whiskers were introduced into the SiC fiber preform by gel injection molding process to obtain a porous composite material. The porous composite material is placed in the first polycarbosilane slurry for multiple immersion and cracking to obtain a semi-dense SiC f / SiC composite materials; Semi-dense SiC f The / SiC composite material is placed in the second polycarbosilane slurry for multiple impregnation and cracking to obtain a dense SiC f / SiC composite materials; Each impregnation and cracking process includes: placing the composite material in a first polycarbosilane slurry or a second polycarbosilane slurry, vacuum impregnating, and then pressure impregnating, and then curing and cracking in an argon atmosphere; the mass fraction of the filler in the first polycarbosilane slurry is greater than the mass fraction of the filler in the second polycarbosilane slurry.

[0008] Preferably, the method of introducing SiC whiskers into the SiC fiber preform by using a gel injection molding process comprises: Prepare SiC whisker organic composite slurry; After the SiC whisker organic composite slurry is vacuum stirred to remove bubbles, it is poured into the mold containing the SiC fiber preform, and the SiC whisker organic composite slurry is evenly dispersed in the SiC fiber preform by vibration; the mold is placed in a 75-85 ℃ oven for curing for 2-4 hours; Wherein, the SiC whisker organic composite slurry is prepared according to the following steps: SiC whiskers and pH adjuster tetramethylammonium hydroxide were dissolved in deionized water and ball-milled for 2-4 h to mix evenly. The monomer acrylamide and cross-linking agent methylenebisacrylamide were added and the ball-milling was continued for 5-10 h. Finally, the initiator ammonium persulfate was added.

[0009] Preferably, the first polycarbosilane slurry is prepared according to the following steps: The solid phase active filler silicon powder with a mass fraction of 10% to 15% is added to a liquid phase precursor and mixed evenly to obtain the product; wherein the liquid phase precursor is a mixture of vinyl modified hydrogen polycarbosilane and xylene, and the mass ratio of vinyl modified hydrogen polycarbosilane to xylene is 1:1 to 20; the particle size of the solid phase active filler silicon powder is 100 to 500 nm. Preferably, the second polycarbosilane slurry is prepared according to the following steps: The solid phase active filler silicon powder with a mass fraction of 5% to 10% is added to a liquid phase precursor and mixed evenly to obtain the product; wherein the liquid phase precursor is a mixture of vinyl modified hydrogen polycarbosilane and xylene, and the mass ratio of vinyl modified hydrogen polycarbosilane to xylene is 1:1 to 20; the particle size of the solid phase active filler silicon powder is 100 to 500 nm. Preferably, the vacuum impregnation process comprises: The porous composite material is placed in an impregnation device, and vacuum is drawn until the pressure in the impregnation device is lower than -0.09 MPa. After maintaining the pressure for 20 to 30 minutes, the porous composite material is immersed in the first polycarbosilane slurry or the second polycarbosilane slurry for 20 to 30 minutes and then taken out.

[0010] Preferably, the pressure impregnation process is: placing the porous composite material together with the first polycarbosilane slurry or the second polycarbosilane slurry into a closed container, pressurizing it to 1-3 MPa, and taking it out after maintaining it for 30-60 minutes.

[0011] Preferably, the solidification and cracking process comprises: The argon flow rate was 150 mL / min, and the temperature program was as follows: increase from room temperature to 220 °C at 10 °C / min, keep warm for 1 h, increase from 220 °C to 1100-1500 °C at 10 °C / min, keep warm for 2 h, decrease from 1100-1500 °C to 700 °C at 5 °C / min, and then cool naturally; Wherein, the impregnation and cracking are performed multiple times, and at least twice.

[0012] Preferably, when the CVI-BN interface phase is prepared in the SiC fiber preform by chemical vapor infiltration process, BCl3 is used as the boron source, NH3 is used as the nitrogen source, H2 and Ar are used as the dilution gases, the deposition temperature is 500~700 °C, the pressure is 2~6 kPa, and the deposition time is 20~40 h; wherein the thickness of the interface phase is 150~500 nm.

[0013] The second object of the present invention is to provide a SiC matrix having high strength and high modulus f / SiC composite materials.

[0014] The third object of the present invention is to provide a SiC matrix containing high strength and high modulus f Application of SiC composite materials in hot end components of aircraft engines.

[0015] Compared with the prior art, the present invention has the following beneficial effects: The present invention provides a SiC matrix having high strength and high modulus f / SiC composite material and preparation method and application thereof, the present invention first deposits BN interface phase in the fiber preform, and deposits a high volume fraction of SiC w Inert filler preparation of SiC w The organic slurry is introduced into the fiber preform by gel injection molding, and then the polycarbosilane slurry modified with active filler silicon powder is introduced into the porous composite material by vacuum impregnation and pressure impregnation. After multiple rounds of impregnation and cracking, the densification is completed. w The introduction of silicon powder promotes the formation of a continuous rigid carrier skeleton, and the introduction of silicon powder significantly reduces the defect content (cracks, pores, etc.) of the matrix, and improves the crystallinity and purity of the PIP-SiC matrix. Through the synergistic effect of the two fillers, not only a PIP-SiC matrix with high strength and high modulus is obtained, but also the internal stress generated during the preparation of the PIP-SiC matrix can be improved. The present invention solves the problem of preparing SiC by PIP method. f / SiC composite materials have low matrix strength, low modulus and poor load transfer efficiency, which effectively improves the SiC f Mechanical properties of SiC composites.

[0016] The present invention adopts gel injection molding method to significantly improve SiC w The amount of SiC introduced (volume fraction of 5~20 vol.%) and its uniform distribution promote the formation of a continuous rigid load-carrying skeleton in the matrix. w The addition of can reduce the sensitivity of PIP-SiC matrix to cracks, increase the cracking energy of PIP-SiC matrix, increase the crack propagation path, and effectively improve SiC f Matrix strength of SiC composites.

[0017] The present invention can control the active filler silicon powder and SiC by accurately controlling the amount of silicon powder introduced and the particle size. w The reaction process between the residual carbon in the organic slurry and the free carbon generated during the cracking of PCS is used to prepare a PIP-SiC matrix with pure components, further improving the modulus of the PIP-SiC matrix.

[0018] The SiC crystals generated by the silicon-carbon reaction provided by the present invention are attached to the SiC w Around it, the rigid skeleton inside the matrix is ​​further strengthened, and the loading effect of PIP-SiC is improved.

[0019] The heat release of the silicon-carbon reaction provided by the present invention can improve the crystallinity and grain size of SiC. The thermal conductivity and intrinsic strength of SiC with high crystallinity and large grain size are higher than those of amorphous SiC, which helps to reduce the f The influence of thermal stress on high temperature application of SiC composite materials f / SiC composites properties.

[0020] The volume expansion effect of the present invention during the silicon-carbon reaction process can inhibit the stress generated by the contraction during PCS cracking to a certain extent, and reduce matrix cracks and holes. This is not only conducive to improving SiC f The overall density of the PIP-SiC composite material is improved (the porosity is not higher than 10%), and it helps to improve the structural integrity of the PIP-SiC matrix, reduce the matrix defect content, and improve the overall modulus and matrix load transfer efficiency of the PIP-SiC matrix.

[0021] The silicon powder provided by the present invention is used as an active filler, and the raw material cost is low, and the silicon powder introduction process is simple and easy to implement, which is consistent with the advantages of the PIP method, such as low cost, simple process operation, and the ability to manufacture components of complex shapes. The unmodified PIP process has low efficiency and a long densification cycle, and requires multiple rounds of impregnation and cracking to achieve high density. The addition of the two fillers in the present invention can effectively shorten the PIP densification cycle and further reduce the manufacturing cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 The present invention is a process flow chart of the preparation method.

[0023] Figure 2 PIP SiC with high strength and high modulus matrix f Schematic diagram of the structure of / SiC composite material.

[0024] Figure 3 The SiC introduced into the fiber preform by gel injection molding in Example 2 w Scanning electron microscope image.

[0025] Figure 4 SiC prepared in Comparative Example 1 and Example 2 f Scanning electron microscope image of the polished cross section of the PIP-SiC matrix in the / SiC composite material.

[0026] Figure 5 The modified SiC prepared in Example 2 f Bending stress-displacement curves of / SiC composite materials.

[0027] Figure 6 The modified SiC prepared in Example 2 f Tensile stress-strain curves of / SiC composites. DETAILED DESCRIPTION

[0028] In order to enable those skilled in the art to better understand and implement the technical solution of the present invention, the present invention is further described below in conjunction with specific embodiments and drawings, but the embodiments are not intended to limit the present invention.

[0029] In order to solve the problems of low strength, low modulus and poor load transfer efficiency of the composite material prepared by the PIP method, the present invention proposes a SiC matrix containing a high strength and high modulus matrix. f / SiC composites. By combining inert filler SiC w The PIP-SiC matrix is ​​modified together with the active filler silicon powder, which promotes the formation of a continuous rigid load-carrying skeleton in the matrix, reduces the defect content of the matrix, improves the crystallinity, and purifies the components. The mechanical properties of the modified composite material are improved by more than 30%.

[0030] In order to achieve the above-mentioned object, the present invention provides a SiC matrix having high strength and high modulus. f A method for preparing a SiC composite material comprises the following steps: The CVI-BN interface phase was prepared in the SiC fiber preform by chemical vapor infiltration process, and SiC whiskers were introduced into the SiC fiber preform by gel injection molding process to obtain a porous composite material. The porous composite material is placed in the first polycarbosilane slurry for multiple immersion and cracking to obtain a semi-dense SiC f / SiC composite materials; Semi-dense SiC f The / SiC composite material is placed in the second polycarbosilane slurry for multiple impregnation and cracking to obtain a dense SiC f / SiC composite materials; Each impregnation and cracking process includes: placing the composite material in a first polycarbosilane slurry or a second polycarbosilane slurry, vacuum impregnating, and then pressure impregnating, and then curing and cracking in an argon atmosphere; the mass fraction of the filler in the first polycarbosilane slurry is greater than the mass fraction of the filler in the second polycarbosilane slurry.

[0031] The method of introducing SiC whiskers into the SiC fiber preform by using a gel injection molding process comprises: Prepare SiC whisker organic composite slurry; After the SiC whisker organic composite slurry is vacuum stirred to remove bubbles, it is poured into the mold containing the SiC fiber preform, and the SiC whisker organic composite slurry is evenly dispersed in the SiC fiber preform by vibration; the mold is placed in a 75-85 ℃ oven for curing for 2-4 hours; Wherein, the SiC whisker organic composite slurry is prepared according to the following steps: SiC whiskers and pH adjuster tetramethylammonium hydroxide were dissolved in deionized water and ball-milled for 2-4 h to mix evenly. The monomer acrylamide and cross-linking agent methylenebisacrylamide were added and the ball-milling was continued for 5-10 h. Finally, the initiator ammonium persulfate was added.

[0032] The first polycarbosilane slurry is prepared according to the following steps: The solid phase active filler silicon powder with a mass fraction of 10% to 15% is added to a liquid phase precursor and mixed evenly to obtain the product; wherein the liquid phase precursor is a mixture of vinyl modified hydrogen polycarbosilane and xylene, and the mass ratio of vinyl modified hydrogen polycarbosilane to xylene is 1:1 to 20; the particle size of the solid phase active filler silicon powder is 100 to 500 nm. The second polycarbosilane slurry is prepared according to the following steps: The solid phase active filler silicon powder with a mass fraction of 5% to 10% is added to a liquid phase precursor and mixed evenly to obtain the product; wherein the liquid phase precursor is a mixture of vinyl modified hydrogen polycarbosilane and xylene, and the mass ratio of vinyl modified hydrogen polycarbosilane to xylene is 1:1 to 20; the particle size of the solid phase active filler silicon powder is 100 to 500 nm. The vacuum impregnation process comprises: The porous composite material is placed in an impregnation device, and vacuum is drawn until the pressure in the impregnation device is lower than -0.09 MPa. After maintaining the pressure for 20 to 30 minutes, the porous composite material is immersed in the first polycarbosilane slurry or the second polycarbosilane slurry for 20 to 30 minutes and then taken out.

[0033] The pressure impregnation process is as follows: placing the porous composite material together with the first polycarbosilane slurry or the second polycarbosilane slurry into a closed container, pressurizing it to 1-3 MPa, and taking it out after maintaining it for 30-60 minutes.

[0034] The solidification and cracking process comprises: The argon flow rate was 150 mL / min, and the temperature program was as follows: increase from room temperature to 220 °C at 10 °C / min, keep warm for 1 h, increase from 220 °C to 1100-1500 °C at 10 °C / min, keep warm for 2 h, decrease from 1100-1500 °C to 700 °C at 5 °C / min, and then cool naturally.

[0035] Wherein, the impregnation and cracking are performed multiple times, and at least twice.

[0036] When the CVI-BN interface phase is prepared in the SiC fiber preform by chemical vapor infiltration process, BCl3 is used as the boron source, NH3 is used as the nitrogen source, H2 and Ar are used as the dilution gases, the deposition temperature is 500~700 ℃, the pressure is 2~6 kPa, and the deposition time is 20~40 h; the thickness of the interface phase is 150~500 nm.

[0037] In one embodiment, see Figure 1 As shown, a SiC matrix with high strength and high modulus f A method for preparing a SiC composite material, the specific steps comprising: Step 1: Prepare CVI-BN interface phase in SiC fiber preform by chemical vapor infiltration process; The fiber preform is one of a unidirectional SiC fiber preform, a two-dimensional SiC fiber preform or a three-dimensional four-directional SiC fiber preform, wherein the fiber volume fraction is 30% to 50%.

[0038] The preparation process of CVI-BN interface phase is chemical vapor infiltration process, using BCl3 as boron source, NH3 as nitrogen source, H2 and Ar as dilution gas, deposition temperature of 500~700 ℃, pressure of 2~6 kPa, deposition time of 20~40 h; among which, the thickness of interface phase is 150~500 nm.

[0039] Step 2: Configure SiC Whiskers (SiC w ) organic slurry; SiC is introduced into the SiC fiber preform by gel injection molding process w , SiC w The volume fraction in the composite material is 5%~20%, resulting in a density of 1.9~2.1 g / cm 3 porous composite materials; SiC w The method of preparing the organic composite slurry is as follows: w , pH regulator tetramethylammonium hydroxide TMAH was dissolved in deionized water, ball milled for 2-4 h, and mixed evenly to obtain SiCw Organic slurry; Towards SiC w Add monomer acrylamide AM and crosslinking agent methylene bisacrylamide MBAM to the organic slurry and continue to ball mill for 5-10 h; finally add initiator ammonium persulfate APS to obtain SiC w Organic composite slurry; wherein SiC w The ratio of organic slurry is: SiC w The mass fraction is 30%~70%, the mass fraction of tetramethylammonium hydroxide is 1%~3%, the mass fraction of acrylamide is 3%~10%, the mass fraction of methylenebisacrylamide is 0.4%~1%, and the mass fraction of ammonium persulfate is 0.4%~1%.

[0040] The gel casting process is as follows: SiC w After the organic slurry is vacuum stirred to remove bubbles, it is poured into the mold containing the fiber preform, and the SiC w The organic slurry is evenly dispersed in the fiber preform; the mold is placed in an oven at 80°C for curing for 2-4 hours, and finally the fiber preform is taken out from the mold; Step 3: Introducing SiC w The porous composite material is vacuum impregnated in the polycarbosilane slurry (first polycarbosilane slurry) for 1 hour, then immersed in the polycarbosilane slurry for pressure impregnation for 1 hour, and then ultrasonicated for 10 minutes; the excess slurry on the surface of the composite material is wiped off, and the composite material is placed in a tube furnace for solidification and cracking in an argon atmosphere; The preparation method of polycarbosilane slurry is as follows: adding 10% to 15% by mass of solid active filler silicon powder into a liquid precursor, wherein the liquid precursor is a mixture of vinyl-modified hydrogen polycarbosilane and xylene, and the mass ratio of vinyl-modified hydrogen polycarbosilane to xylene is 1:20 to 1:1; The vacuum impregnation process is as follows: placing the porous composite material in an impregnation device, evacuating the device until the pressure inside the device is lower than -0.09 MPa, maintaining the pressure for 20 to 30 minutes, and then immersing the porous composite material in polycarbosilane slurry for 20 to 30 minutes before taking it out; The pressure impregnation process is as follows: put the porous composite material together with the polycarbosilane slurry into a closed container and pressurize it to 1-3 MPa, keep it for 30-60 min and then take it out; The solidification and cracking process was as follows: the argon flow rate was 150 mL / min, the temperature program was 10 °C / min from room temperature to 220 °C, kept at this temperature for 1 h, 10 °C / min from 220 °C to 1100-1500 °C, kept at this temperature for 2 h, 5 °C / min from 1100-1500 °C to 700 °C, and then cooled naturally; The particle size of the solid phase filler silicon powder in step 3 is 100~500 nm. Nano-scale silicon powder filler can be enriched around SiCw and w The organic matter in the organic slurry converts the residual carbon into a reaction to form large-sized β-SiC grains, thereby improving the loading effect of the matrix.

[0041] Step 4: Remove the PIP residue attached to the surface of the composite material, and repeatedly immerse and crack for 2 to 5 times to obtain a density of 2.1 to 2.4 g / cm 3 Semi-dense SiC f / SiC composite materials; Reduce the mass fraction of silicon powder filler in the polycarbosilane slurry (second polycarbosilane slurry), repeat step 3, and repeatedly impregnate and crack for 2 to 5 times to obtain dense SiC f / SiC composite materials.

[0042] In the polycarbosilane slurry in step 4, the mass fraction of silicon powder is reduced to 5% to 10%. w After the organic matter in the organic slurry is completely converted into residual carbon, the silicon powder only reacts with the free carbon generated during the PCS cracking process. In order to keep the SiC phase in the PIP-SiC matrix close to the stoichiometric ratio, the required silicon powder content is reduced.

[0043] The second aspect of the present invention provides a SiC matrix containing high strength and high modulus f / SiC composite materials.

[0044] See also Figure 2 As shown, the SiC f The matrix of the SiC composite material is composed of SiC w It forms a continuous rigid load-carrying skeleton with β-SiC grains with a grain size greater than 50 nm. The surface of the skeleton is wrapped by a SiC filling phase with few defects (cracks and pores), a crystallinity greater than 80% and a near-stoichiometric ratio. The skeleton and the filling phase together form a PIP-SiC matrix with high strength and high modulus.

[0045] The PIP-SiC matrix modulus in the composite material is greater than 280 GPa, the matrix cracking stress of the composite material is greater than 140 MPa, and the density is greater than 2.6 g / cm 3 , open porosity is less than 10%.

[0046] The third aspect of the present invention provides a SiC matrix containing high strength and high modulus f Application of SiC composite materials in hot end components of aircraft engines.

[0047] It should be noted that the experimental methods used in the present invention are all conventional methods unless otherwise specified; the reagents and materials used are all commercially available unless otherwise specified.

[0048] Example 1 Step 1 SiC f Preparation of SiC fiber preform Step 1.1: Weave SiC fibers to obtain a unidirectional fiber preform with a fiber volume fraction of 35%.

[0049] Step 1.2: The BN interface phase is prepared in the SiC fiber preform by chemical vapor infiltration process, wherein BCl3 is the boron source, NH3 is the nitrogen source, H2 and Ar are the dilution gases, the deposition temperature is 600 °C, the pressure is 4 kPa, and the deposition time is 40 h. The thickness of the BN interface phase obtained is 300 nm.

[0050] Step 2: Gel casting process to introduce SiC w : Step 2.1 SiC with a mass fraction of 45 wt.% w , 1.5 wt.% of pH adjuster tetramethylammonium hydroxide TMAH was dissolved in deionized water, and an appropriate amount of zirconium oxide ball milling beads were added and put into a ball mill jar for wet grinding for 4 h.

[0051] Step 2.2 Add 6 wt.% of monomer acrylamide AM and 0.5 wt.% of crosslinker methylene bisacrylamide MBAM to SiC w The ball milling was continued for 10 h in the organic slurry.

[0052] Step 2.3 To SiC w 0.5 wt.% of initiator ammonium persulfate was added to the organic slurry, and after vacuum stirring to remove bubbles, it was poured into the mold containing the fiber preform to vibrate the SiC w The organic slurry was evenly dispersed in the fiber preform; the mold was placed in an oven at 80°C for curing for 3 h. Finally, the fiber preform was taken out of the mold to obtain a density of 2.09 g / cm 3 porous composite materials.

[0053] Step 3: Impregnation and cracking of polycarbosilane slurry: Step 3.1: Vinyl-modified hydrogen polycarbosilane and xylene were mixed evenly in a mass ratio of 1:3, and magnetically stirred at room temperature for 20 minutes to prepare a liquid precursor. Then, solid active filler silicon powder with a mass fraction of 10 wt.% and a particle size of 100 nm was added to the liquid precursor, and magnetically stirred at room temperature for 20 minutes to prepare a polycarbosilane slurry for impregnation.

[0054] Step 3.2: Place the porous composite material into an impregnation device, evacuate the device until the pressure inside is lower than -0.09 MPa, and maintain for 30 minutes. Then, immerse the porous composite material into the polycarbosilane slurry and maintain for 30 minutes before taking it out.

[0055] Step 3.3: Place the porous composite material together with the polycarbosilane slurry into a sealed container and pressurize it to 1 MPa, then take it out after keeping it for 60 minutes.

[0056] Step 3.4: Wipe off the excess slurry on the surface of the porous composite material obtained in step 3.3, put it into a tubular furnace, and solidify and crack it in an argon atmosphere with an argon gas flow rate of 150 mL / min. The heating program is 10°C / min from room temperature to 220°C, keep it warm for 1h, 10°C / min from 220°C to 1100°C, keep it warm for 1h, cool it from 1100°C to 700°C at 5°C / min, and then cool it naturally.

[0057] Step 4: Repeated immersion and cracking: Step 4.1 Remove the PIP residue attached to the surface of the composite material obtained in step 3, and repeat the immersion and cracking for 3 rounds to obtain a density of 2.36 g / cm 3 Semi-dense SiC f / SiC composite materials.

[0058] Step 4.2 Reduce the mass fraction of silicon powder filler in the polycarbosilane slurry to 5 wt.%, repeat step 3, and repeat the impregnation and cracking for 5 times to obtain dense SiC f / SiC composite materials.

[0059] The final SiC f The density of the / SiC composite material is 2.69 g / cm 3 The open porosity is 5.44%. f The modulus of the PIP-SiC matrix in the SiC / SiC composite is 302.2±17.4 GPa, the matrix cracking stress is 155.2±11.1 MPa, the bending strength is 1311.6±115.2 MPa, and the fracture toughness is 48.6±6.1 MPa·m 1 / 2 , the tensile strength is 630.7±48.7 MPa.

[0060] Example 2 Step 1 SiC f Preparation of SiC fiber preform Step 1.1 Weave SiC fibers to obtain a two-dimensional fiber preform. The fiber volume fraction is 35%.

[0061] Step 1.2: The BN interface phase is prepared in the SiC fiber preform by chemical vapor infiltration process, wherein BCl3 is the boron source, NH3 is the nitrogen source, H2 and Ar are the dilution gases, the deposition temperature is 600 °C, the pressure is 4 kPa, and the deposition time is 40 h. The thickness of the BN interface phase obtained is 300 nm.

[0062] Step 2: Gel casting process to introduce SiC w : Step 2.1 SiC with a mass fraction of 45 wt.% w , 1.5 wt.% of pH adjuster tetramethylammonium hydroxide TMAH was dissolved in deionized water, and an appropriate amount of zirconium oxide ball milling beads were added and put into a ball mill jar for wet grinding for 4 h.

[0063] Step 2.2 Add 6 wt.% of monomer acrylamide AM and 0.5 wt.% of crosslinker methylene bisacrylamide MBAM to SiC w The ball milling was continued for 10 h in the organic slurry.

[0064] Step 2.3 To SiC w 0.5 wt.% of initiator ammonium persulfate was added to the organic slurry, and after vacuum stirring to remove bubbles, it was poured into the mold containing the fiber preform to vibrate the SiC w The organic slurry was evenly dispersed inside the fiber preform; the mold was placed in an oven at 80°C for curing for 3 h. Finally, the fiber preform was taken out of the mold to obtain a density of 2.03 g / cm 3 porous composite materials.

[0065] Step 3: Impregnation and cracking of polycarbosilane slurry: Step 3.1: Vinyl-modified hydrogen polycarbosilane and xylene were mixed evenly in a mass ratio of 1:3, and magnetically stirred at room temperature for 20 minutes to prepare a liquid precursor. Then, solid active filler silicon powder with a mass fraction of 10 wt.% and a particle size of 100 nm was added to the liquid precursor, and magnetically stirred at room temperature for 20 minutes to prepare a polycarbosilane slurry for impregnation.

[0066] Step 3.2: Place the porous composite material into an impregnation device, evacuate the device until the pressure inside is lower than -0.09 MPa, and maintain for 30 minutes. Then, immerse the porous composite material into the polycarbosilane slurry and maintain for 30 minutes before taking it out.

[0067] Step 3.3: Place the porous composite material together with the polycarbosilane slurry into a sealed container and pressurize it to 1 MPa, then take it out after keeping it for 60 minutes.

[0068] Step 3.4: Wipe off the excess slurry on the surface of the porous composite material obtained in step 3.3, put it into a tubular furnace, and solidify and crack it in an argon atmosphere with an argon gas flow rate of 150 mL / min. The heating program is 10°C / min from room temperature to 220°C, keep it warm for 1h, 10°C / min from 220°C to 1100°C, keep it warm for 1h, cool it from 1100°C to 700°C at 5°C / min, and then cool it naturally.

[0069] Step 4: Repeated immersion and cracking: Step 4.1 Remove the PIP residue attached to the surface of the composite material obtained in step 3, and repeat the immersion and cracking for 4 rounds to obtain a density of 2.32 g / cm 3 Semi-dense SiC f / SiC composite materials.

[0070] Step 4.2 Reduce the mass fraction of silicon powder filler in the polycarbosilane slurry to 5 wt.%, repeat step 3, and repeat the impregnation and cracking for 5 times to obtain dense SiC f / SiC composite materials.

[0071] The final SiC f The density of the / SiC composite material is 2.64 g / cm 3 The open porosity is 6.21%. f The matrix modulus of the PIP-SiC / SiC composite is 327.7±11.9 GPa, the matrix cracking stress is 167.7±8.3 MPa, the bending strength is 857.1±36.2 MPa, and the fracture toughness is 43.9±3.1 MPa·m 1 / 2 , the tensile strength is 492.8±22.2 MPa.

[0072] Example 3 Step 1 SiC f Preparation of SiC fiber preform Step 1.1 Weave SiC fibers to obtain a three-dimensional four-directional fiber preform. The fiber volume fraction is 35%.

[0073] Step 1.2: The BN interface phase is prepared in the SiC fiber preform by chemical vapor infiltration process, wherein BCl3 is the boron source, NH3 is the nitrogen source, H2 and Ar are the dilution gases, the deposition temperature is 600 °C, the pressure is 4 kPa, and the deposition time is 40 h. The thickness of the BN interface phase obtained is 300 nm.

[0074] Step 2: Gel casting process to introduce SiC w : Step 2.1 SiC with a mass fraction of 45 wt.% w , 1.5 wt.% of pH adjuster tetramethylammonium hydroxide TMAH was dissolved in deionized water, and an appropriate amount of zirconium oxide ball milling beads were added and put into a ball mill jar for wet grinding for 4 h.

[0075] Step 2.2 Add 6 wt.% of monomer acrylamide AM and 0.5 wt.% of crosslinker methylene bisacrylamide MBAM to SiC w The ball milling was continued for 10 h in the organic slurry.

[0076] Step 2.3 To SiC w 0.5 wt.% of initiator ammonium persulfate was added to the organic slurry, and after vacuum stirring to remove bubbles, it was poured into the mold containing the fiber preform to vibrate the SiC w The organic slurry was evenly dispersed inside the fiber preform; the mold was placed in an oven at 80°C for 3 h for curing. Finally, the fiber preform was taken out of the mold to obtain a density of 2.02 g / cm 3 porous composite materials.

[0077] Step 3: Impregnation and cracking of polycarbosilane slurry: Step 3.1: Vinyl-modified hydrogen polycarbosilane and xylene were mixed evenly in a mass ratio of 1:3, and magnetically stirred at room temperature for 20 minutes to prepare a liquid precursor. Then, solid active filler silicon powder with a mass fraction of 10 wt.% and a particle size of 100 nm was added to the liquid precursor, and magnetically stirred at room temperature for 20 minutes to prepare a polycarbosilane slurry for impregnation.

[0078] Step 3.2: Place the porous composite material into an impregnation device, evacuate the device until the pressure inside is lower than -0.09 MPa, and maintain for 30 minutes. Then, immerse the porous composite material into the polycarbosilane slurry and maintain for 30 minutes before taking it out.

[0079] Step 3.3: Place the porous composite material together with the polycarbosilane slurry into a sealed container and pressurize it to 1 MPa, then take it out after keeping it for 60 minutes.

[0080] Step 3.4: Wipe off the excess slurry on the surface of the porous composite material obtained in step 3.3, put it into a tubular furnace, and solidify and crack it in an argon atmosphere with an argon gas flow rate of 150 mL / min. The heating program is 10°C / min from room temperature to 220°C, keep it warm for 1h, 10°C / min from 220°C to 1100°C, keep it warm for 1h, cool it from 1100°C to 700°C at 5°C / min, and then cool it naturally.

[0081] Step 4: Repeated immersion and cracking: Step 4.1 Remove the PIP residue attached to the surface of the composite material obtained in step 3, and repeat the immersion and cracking for 4 rounds to obtain a density of 2.34 g / cm 3 Semi-dense SiC f / SiC composite materials.

[0082] Step 4.2 Reduce the mass fraction of silicon powder filler in the polycarbosilane slurry to 5 wt.%, repeat step 3, and repeat the impregnation and cracking for 5 times to obtain dense SiC f / SiC composite materials.

[0083] The final SiC f The density of the / SiC composite material is 2.65 g / cm 3 , the open porosity is 6.12%. f The matrix modulus of the PIP-SiC / SiC composite is 296.5±3.8 GPa, the matrix cracking stress is 156.3±9.6 MPa, the bending strength is 846.5±48.8 MPa, and the fracture toughness is 45.2±2.4 MPa·m 1 / 2 , the tensile strength is 470.8±59.7 MPa.

[0084] Comparative Example 1 Step 1 SiC f Preparation of SiC fiber preform Step 1.1 Weave SiC fibers to obtain a two-dimensional fiber preform. The fiber volume fraction is 35%.

[0085] Step 1.2: The BN interface phase is prepared in the SiC fiber preform by chemical vapor infiltration process, wherein BCl3 is the boron source, NH3 is the nitrogen source, H2 and Ar are the dilution gases, the deposition temperature is 600 °C, the pressure is 4 kPa, and the deposition time is 40 h. The thickness of the BN interface phase obtained is 300 nm.

[0086] Step 2: Impregnation and cleavage of polycarbosilane solution: Step 2.1: Vinyl-modified hydrogen polycarbosilane and xylene are uniformly mixed in a mass ratio of 1:3, and magnetically stirred at room temperature for 20 minutes to obtain a polycarbosilane solution.

[0087] Step 2.2: Place the porous composite material into an impregnation device, evacuate the device until the pressure inside is lower than -0.09 MPa, and maintain for 30 minutes. Then, immerse the porous composite material in a polycarbosilane solution and maintain for 30 minutes before taking it out.

[0088] Step 2.3: Place the porous composite material together with the polycarbosilane solution into a sealed container and pressurize it to 1 MPa, then take it out after keeping it for 60 minutes.

[0089] Step 2.4: Wipe off the excess solution on the surface of the porous composite material obtained in step 2.3, place it in a tubular furnace, and solidify and crack it in an argon atmosphere with an argon gas flow rate of 150 mL / min. The heating program is 10°C / min from room temperature to 220°C, keep it warm for 1h, 10°C / min from 220°C to 1100°C, keep it warm for 1h, cool it down from 1100°C to 700°C at 5°C / min, and then cool it naturally.

[0090] Step 3: Repeated immersion and cracking: The PIP residue attached to the surface of the composite material obtained in step 2 was removed, and the immersion and cracking were repeated for 15 rounds to obtain a density of 2.65 g / cm 3 Dense SiC f / SiC composite materials.

[0091] The final SiC f The density of the / SiC composite material is 2.65 g / cm 3 , the open porosity is 6.01%. f The matrix modulus of the PIP-SiC / SiC composite is 207.1±8.3 GPa, the matrix cracking stress is 110.1±5.9 MPa, the bending strength is 505.1±76.8 MPa, and the fracture toughness is 22.2±3.1 MPa·m 1 / 2 , the tensile strength is 246.2±36.7 MPa.

[0092] Figure 4 The photos show the cross-sectional morphology of the PIP-SiC matrix of the composite material before and after modification in Example 2 and Comparative Example 1. In Comparative Example 1, there are a large number of cracks and holes in the PIP-SiC matrix, which seriously affects the matrix load transfer efficiency. The measured matrix modulus, matrix cracking stress and mechanical properties of the composite material are much lower than those of the modified composite material. In addition, the PIP process before modification has many impregnation and cracking furnaces (15 times), and the composite material preparation cycle is long.

[0093] Comparative Example 2 Step 1 SiC f Preparation of SiC fiber preform Step 1.1 Weave SiC fibers to obtain a two-dimensional fiber preform. The fiber volume fraction is 35%.

[0094] Step 1.2: The BN interface phase is prepared in the SiC fiber preform by chemical vapor infiltration process, wherein BCl3 is the boron source, NH3 is the nitrogen source, H2 and Ar are the dilution gases, the deposition temperature is 600 °C, the pressure is 4 kPa, and the deposition time is 40 h. The thickness of the BN interface phase obtained is 300 nm.

[0095] Step 2: Gel casting process to introduce SiC w : Step 2.1 SiC with a mass fraction of 45 wt.% w , 1.5 wt.% of pH adjuster tetramethylammonium hydroxide TMAH was dissolved in deionized water, and an appropriate amount of zirconium oxide ball milling beads were added and put into a ball mill jar for wet grinding for 4 h.

[0096] Step 2.2 Add 6 wt.% of monomer acrylamide AM and 0.5 wt.% of crosslinker methylene bisacrylamide MBAM to SiC w The ball milling was continued for 10 h in the organic slurry.

[0097] Step 2.3 To SiC w 0.5 wt.% of initiator ammonium persulfate was added to the organic slurry, and after vacuum stirring to remove bubbles, it was poured into the mold containing the fiber preform to vibrate the SiC w The organic slurry was evenly dispersed inside the fiber preform; the mold was placed in an oven at 80°C for curing for 3 h. Finally, the fiber preform was taken out of the mold and a density of 2.08 g / cm 3 porous composite materials.

[0098] Step 3: Impregnation and cleavage of polycarbosilane solution: Step 3.1: Vinyl-modified hydrogen polycarbosilane and xylene were mixed evenly in a mass ratio of 1:3 and magnetically stirred at room temperature for 20 min to obtain a polycarbosilane solution. Step 3.2: Place the porous composite material into an impregnation device, evacuate the device until the pressure inside is lower than -0.09 MPa, and maintain for 30 minutes. Then, immerse the porous composite material in a polycarbosilane solution and maintain for 30 minutes before taking it out.

[0099] Step 3.3: Place the porous composite material together with the polycarbosilane solution into a sealed container and pressurize it to 1 MPa, then take it out after keeping it for 60 minutes.

[0100] Step 3.4: Wipe off the excess solution on the surface of the porous composite material obtained in step 3.3, place it in a tubular furnace, and solidify and crack it in an argon atmosphere with an argon gas flow rate of 150 mL / min. The heating program is 10°C / min from room temperature to 220°C, keep it warm for 1h, 10°C / min from 220°C to 1100°C, keep it warm for 1h, cool it from 1100°C to 700°C at 5°C / min, and then cool it naturally.

[0101] Step 4: Repeated immersion and cracking: Step 4.1 Remove the PIP residue attached to the surface of the composite material obtained in step 3, and repeat the immersion and cracking for 8 rounds to obtain a density of 2.61 g / cm 3 Dense SiC f / SiC composite materials.

[0102] The final SiC f The density of the / SiC composite material is 2.61 g / cm 3 , the open porosity is 7.29%. f The matrix modulus of the PIP-SiC / SiC composite is 248.5±13.2 GPa, the matrix cracking stress is 119.2±8.1 MPa, the bending strength is 506.1±84.1 MPa, and the fracture toughness is 23.6±2.5 MPa·m 1 / 2 , the tensile strength is 265.4±13.2 MPa.

[0103] Adding SiC w After SiC w A continuous skeleton structure is formed inside the PIP-SiC matrix, and the matrix modulus and matrix cracking stress of the composite PIP-SiC are improved compared with the unmodified composite. w The PIP-SiC matrix nearby still has problems such as high defect content, low crystallinity and impure components. w It is difficult to effectively improve the mechanical properties of composite materials as fillers.

[0104] Comparative Example 3 Step 1 SiC f Preparation of SiC fiber preform Step 1.1 Weave SiC fibers to obtain a two-dimensional fiber preform. The fiber volume fraction is 35%.

[0105] Step 1.2: The BN interface phase is prepared in the SiC fiber preform by chemical vapor infiltration process, wherein BCl3 is the boron source, NH3 is the nitrogen source, H2 and Ar are the dilution gases, the deposition temperature is 600 °C, the pressure is 4 kPa, and the deposition time is 40 h. The thickness of the BN interface phase obtained is 300 nm.

[0106] Step 2: Impregnation and cracking of polycarbosilane slurry: Step 2.1: Vinyl-modified hydrogen polycarbosilane and xylene were mixed evenly in a mass ratio of 1:3, and magnetically stirred for 20 minutes at room temperature to prepare a liquid precursor. Then, solid active filler silicon powder with a mass fraction of 5 wt.% and a particle size of 100 nm was added to the liquid precursor, and magnetically stirred for 20 minutes at room temperature to prepare a polycarbosilane slurry for impregnation.

[0107] Step 2.2: Place the porous composite material into an impregnation device, evacuate the device until the pressure inside is lower than -0.09 MPa, and maintain for 30 minutes. Then, immerse the porous composite material into the polycarbosilane slurry and maintain for 30 minutes before taking it out.

[0108] Step 2.3: Place the porous composite material together with the polycarbosilane slurry into a sealed container and pressurize it to 1 MPa, then take it out after keeping it for 60 minutes.

[0109] Step 2.4: Wipe off the excess slurry on the surface of the porous composite material obtained in step 2.3, put it into a tubular furnace, and solidify and crack it in an argon atmosphere with an argon gas flow rate of 150 mL / min. The heating program is 10 ℃ / min from room temperature to 220 ℃, keep warm for 1 h, 10 ℃ / min from 220 ℃ to 1100 ℃, keep warm for 1 h, cool from 1100 ℃ to 700 ℃ at 5 ℃ / min, and then cool naturally.

[0110] Step 3: Repeated immersion and cracking: The PIP residue attached to the surface of the composite material obtained in step 2 was removed, and the immersion and cracking were repeated for 11 rounds to obtain a density of 2.62 g / cm 3 Dense SiC f / SiC composite materials.

[0111] The final SiC f The density of the / SiC composite material is 2.62 g / cm 3 , the open porosity is 5.93%. f The matrix modulus of the PIP-SiC / SiC composite is 234.7±11.7 GPa, the matrix cracking stress is 123.4±6.2 MPa, the bending strength is 591.2±78.3 MPa, and the fracture toughness is 28.3±2.2 MPa·m1 / 2 , the tensile strength is 302.8±28.5 MPa.

[0112] After adding silicon powder, the number of cracks and pores inside the matrix of the composite material PIP-SiC decreased, the SiC crystallinity increased, and the SiC phase in the matrix was close to the stoichiometric ratio. The matrix modulus, matrix cracking stress and mechanical properties of the regulated composite material were all improved. However, the PIP process has many impregnation and cracking furnaces (11 times), the PIP-SiC matrix is ​​loosely distributed, and a continuous rigid skeleton is not formed inside the matrix, making it difficult to transfer loads continuously. Therefore, it is difficult to efficiently improve the mechanical properties of the composite material by only adding silicon powder as a filler.

[0113] In order to illustrate the present invention provides a SiC containing high strength and high modulus matrix f The relevant properties of the SiC composite material are explained in conjunction with the accompanying drawings.

[0114] Figure 3 The SiC introduced into the fiber preform by gel injection molding in Example 2 w Scanning electron microscope image.

[0115] from Figure 3 It can be seen that SiC w It is in the shape of a long rod with a diameter of 1-2 μm and a length of 10-30 μm. w The pores in the preform are evenly distributed, and the pore sizes are mostly between 1-3 μm. The PIP process is used to fill the pores.

[0116] Figure 4 SiC prepared in Comparative Example 1 and Example 2 f Scanning electron microscope image of the polished cross section of the PIP-SiC matrix in the / SiC composite material.

[0117] from Figure 4 It can be seen that there are a large number of cracks and hole defects in the PIP-SiC matrix in Comparative Example 1, and the crack size is about 10-40 μm, and these defects are difficult to fill by repeated impregnation and cracking. In Example 2, the PIP-SiC matrix is ​​smooth and flat, with only a small number of cracks, which is expected to improve the modulus of the matrix and the mechanical properties of the composite material.

[0118] Figure 5 The modified SiC prepared in Example 2 f Bending stress-displacement curves of / SiC composite materials.

[0119] from Figure 5 It can be seen that the SiC prepared in Example 2 fThe flexural strength of the / SiC composite material can reach 857 MPa, which is much higher than that of SiC prepared by the traditional PIP process. f / SiC composite bending properties. After the composite material reaches the highest load, the load decreases in a step-like manner, presenting a pseudo-plastic fracture.

[0120] Figure 6 The modified SiC prepared in Example 2 f Tensile stress-strain curves of / SiC composites.

[0121] Figure 6 It can be seen that the SiC prepared in Example 2 f The tensile strength of the SiC composite material can reach 493 MPa. The 0.005% strain offset method is used to obtain the f The proportional limit stress of the SiC / SiC composite material is 167 MPa. This method significantly improves the SiC prepared by the traditional PIP process. f Tensile strength and proportional limit stress of / SiC composites.

[0122] The present invention describes preferred embodiments and their effects. However, those skilled in the art may make additional changes and modifications to these embodiments once they are aware of the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.

[0123] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A SiC containing a high strength and high modulus matrix f A method for preparing a SiC composite material, characterized in that: The following steps are involved: The CVI-BN interface phase was prepared in the SiC fiber preform by chemical vapor infiltration process, and SiC whiskers were introduced into the SiC fiber preform by gel injection molding process to obtain a porous composite material. The porous composite material is placed in the first polycarbosilane slurry for multiple immersion and cracking to obtain a semi-dense SiC f / SiC composite materials; Semi-dense SiC f The / SiC composite material is placed in the second polycarbosilane slurry for multiple impregnation and cracking to obtain a dense SiC f / SiC composite materials; Each impregnation and cracking process includes: placing the composite material in a first polycarbosilane slurry or a second polycarbosilane slurry, vacuum impregnating, and then pressure impregnating, and then curing and cracking in an argon atmosphere; the mass fraction of the filler in the first polycarbosilane slurry is greater than the mass fraction of the filler in the second polycarbosilane slurry.

2. The SiC containing high strength and high modulus matrix according to claim 1 f A method for preparing a SiC composite material, characterized in that: The method of introducing SiC whiskers into the SiC fiber preform by using a gel injection molding process comprises: Prepare SiC whisker organic composite slurry; After the SiC whisker organic composite slurry is vacuum stirred to remove bubbles, it is poured into the mold containing the SiC fiber preform, and the SiC whisker organic composite slurry is evenly dispersed in the SiC fiber preform by vibration; the mold is placed in a 75-85 ℃ oven for curing for 2-4 hours; Wherein, the SiC whisker organic composite slurry is prepared according to the following steps: SiC whiskers and pH adjuster tetramethylammonium hydroxide were dissolved in deionized water and ball-milled for 2-4 h to mix evenly. The monomer acrylamide and cross-linking agent methylenebisacrylamide were added and the ball-milling was continued for 5-10 h. Finally, the initiator ammonium persulfate was added.

3. The SiC containing high strength and high modulus matrix according to claim 1 f A method for preparing a SiC composite material, characterized in that: The first polycarbosilane slurry is prepared according to the following steps: 10% to 15% by mass of solid phase active filler silicon powder is added to a liquid phase precursor and mixed evenly to obtain the slurry; wherein the liquid phase precursor is a mixture of vinyl-modified hydrogen polycarbosilane and xylene, and the mass ratio of vinyl-modified hydrogen polycarbosilane to xylene is 1:1 to 20; the particle size of the solid phase active filler silicon powder is 100 to 500 nm.

4. The SiC containing high strength and high modulus matrix according to claim 1 f A method for preparing a SiC composite material, characterized in that: The second polycarbosilane slurry is prepared according to the following steps: adding 5% to 10% by mass of solid phase active filler silicon powder to a liquid phase precursor and mixing them evenly to obtain the slurry; wherein the liquid phase precursor is a mixture of vinyl-modified hydrogen polycarbosilane and xylene, and the mass ratio of vinyl-modified hydrogen polycarbosilane to xylene is 1:1 to 20; the particle size of the solid phase active filler silicon powder is 100 to 500 nm.

5. The SiC containing high strength and high modulus matrix according to claim 1 f A method for preparing a SiC composite material, characterized in that: The vacuum impregnation process comprises: placing the porous composite material into an impregnation device, evacuating the device until the pressure inside is lower than -0.09 MPa, maintaining the pressure for 20 to 30 minutes, and then immersing the porous composite material into the first polycarbosilane slurry or the second polycarbosilane slurry for 20 to 30 minutes before taking it out.

6. The SiC containing high strength and high modulus matrix according to claim 1 f A method for preparing a SiC composite material, characterized in that: The pressure impregnation process is as follows: placing the porous composite material together with the first polycarbosilane slurry or the second polycarbosilane slurry into a closed container, pressurizing it to 1-3 MPa, and taking it out after maintaining it for 30-60 minutes.

7. The SiC containing high strength and high modulus matrix according to claim 1 f A method for preparing a SiC composite material, characterized in that: The solidification and cracking process comprises: an argon gas flow rate of 150 mL / min, a temperature rising program of: rising from room temperature to 220°C at 10°C / min, keeping the temperature for 1 hour, rising from 220°C to 1100-1500°C at 10°C / min, keeping the temperature for 2 hours, cooling from 1100-1500°C to 700°C at 5°C / min, and cooling naturally; wherein, multiple impregnation and cracking are performed, and at least two impregnation and cracking are performed.

8. The SiC containing high strength and high modulus matrix according to claim 1 f A method for preparing a SiC composite material, characterized in that: When the CVI-BN interface phase is prepared in the SiC fiber preform by chemical vapor infiltration process, BCl3 is used as the boron source, NH3 is used as the nitrogen source, H2 and Ar are used as the dilution gases, the deposition temperature is 500~700 ℃, the pressure is 2~6 kPa, and the deposition time is 20~40 h; the thickness of the interface phase is 150~500 nm.

9. A SiC containing a high strength and high modulus matrix obtained by the method according to any one of claims 1 to 8 f / SiC composite materials.

10. A SiC containing high strength and high modulus matrix as claimed in claim 9 f Application of SiC composite materials in hot end components of aircraft engines.

Citation Information

Patent Citations

  • Quick preparation method of wave-absorbing ceramic-based composite material with electromagnetic-impedance gradient matrix

    CN109265189A

  • PIP (precursor infiltration and pyrolysis) rapid densification method of SiCf / SiC composite prefab

    CN109485427A

  • Preparation method of high-volume-fraction short-fiber reinforced quasi-isotropic SiCf / SiC composite material

    CN110078516A

  • Rapid preparation method of C / SiC composite material

    CN112047748A

  • Method for preparing silicon carbide-based composite material integral turbine disc based on gel casting pre-strengthening

    CN115141028A

Cited By

  • Preparation method of silicon carbide

    CN119100842A